2008
DOI: 10.1177/0886260508322181
|View full text |Cite
|
Sign up to set email alerts
|

Agreement on Reporting of Physical, Psychological, and Sexual Violence Among White, Black, and Hispanic Couples in the United States

Abstract: This paper examines agreement on reports of male-to-female (MFPV) and female-to-male (FMPV) psychological, physical and sexual violence among White, Black and Hispanic couples in the U.S. Using a probability sample, separate face-to-face interviews were conducted in respondents' homes with both members of 1,025 intact couples living in the 48 contiguous states. The overall survey response rate was 72%. Results indicate that agreement on each of the three types of violence is low, independent of perpetrator's g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 22 publications
13
75
1
Order By: Relevance
“…In the absence of the partner, the participant may deny the incidents of IPV, 39 which might have led to underreporting. Nevertheless, individual interviews have the advantage of preserving confidentiality.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of the partner, the participant may deny the incidents of IPV, 39 which might have led to underreporting. Nevertheless, individual interviews have the advantage of preserving confidentiality.…”
Section: Discussionmentioning
confidence: 99%
“…However, results should be considered inconclusive at best as the available literature presents varying and often conflicting findings Caetano et al, 2009;Caetano et al, 2002;Cunradi et al, 1999;Cunradi et al, 2002;M. R. Duke & Cunradi, 2011;Hancock & Siu, 2009;Kim-Goodwin & Fox, 2009;Sugihara & Warner, 2002).…”
Section: Risk Factors and Developing Culturally Focused Approaches Bymentioning
confidence: 99%
“…Increased participation and satisfaction of Latino offenders in a culturally focused program suggests reason for further investigation into the benefits of culturally based curricula for Latinos. Several studies have addressed risk factors and cultural indicators of IPV in the Latino/Latina community; however, results should be considered inconclusive at best as the available literature presents varying and often conflicting findings Caetano et al, 2009;Caetano et al, 2002;Cunradi et al, 1999;Cunradi et al, 2000;Cunradi et al, 2002; M. R. Duke & Cunradi, 2011;Hancock & Siu, 2009;Kim-Goodwin & Fox, 2009;Sugihara & Warner, 2002). It has been argued that culturally based interventions are important for Latinos because Latino male perpetrators were not accepting of the conventional model's association between patriarchy and male oppression and that enforcement of traditional gender roles is magnified as a coping mechanism during the immigration process.…”
Section: Working With Perpetrators In Racial and Ethnic Minority Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…African American males reported being victims of FMPV at a rate 2.5 times greater than their peers of other minorities, and a rate 62% higher than their white peers (Rennison & Welchans, 2002;West 2012;West 2016;. In African American relationships where IPV was present, 61% reported that the aggression was mutual in nature, resulting in bidirectional IPV (Cateno et al, 2009;West 2012). In relationships where IPV was reported, African American women identified themselves as perpetrators more readily than African-American men, who more often reported themselves as both perpetrators and victims (Cateno et al, 2009;West, 2016).The unique and complex relationship African American females have with IPV is due in part to the high rates of victimization, perpetration, and even higher rates of bidirectional IVP they report (West, 2016).…”
Section: African American Female Perpetrators Of Ipvmentioning
confidence: 99%